Copper-catalyzed mild desulfonylation of vinyl sulfonyl molecules. Issue 13 (8th June 2020) - Jiang, Ying; Fang, Wan-Yin; Rakesh, K. P.; Qin, Hua-Li
Abstract : The first Cu-catalyzed chemical selective desulfonylation of vinyl sulfonyl molecules to olefins was developed using B2 pin2 –water as the reductant. Abstract : The first Cu-catalyzed chemical selective desulfonylation of vinyl sulfonyl fluorides and vinyl sulfonyl compounds to their corresponding olefins was developed using B2 pin2 –water as the reductant. This protocol featured a wide substrate scope, mild conditions and excellent functional group compatibility.